The Effects of Aspirin in Gestation and Reproduction (EAGeR) Trial: A Story of Discovery - Connell, Matthew T.; Sjaarda, Lindsey A.; Radin, Rose G.; Kuhr, Daniel; Mumford, Sunni L.; Plowden, Torie C.; Silver, Robert M.; Schisterman, Enrique F. (Seminars in Reproductive Medicine, 2017)
Human reproduction is an inefficient process. There are several drivers of complications along the path to and during pregnancy, one of which is inflammation. Treatments to mitigate the deleterious effects of aberrant inflammation with something inexpensive and widely available like aspirin could have dramatic global impact. The Effects of Aspirin in Gestation and Reproduction (EAGeR) trial enrolled women aged 18 to 40 years with one to two prior pregnancy losses and no diagnosis of infertility. Patients were randomized to either low-dose aspirin or placebo. Here, we review the collective findings of the EAGeR trial to date and discuss several important lessons learned from the unique data resulting from this groundbreaking trial. Findings reported from this trial provide significant advances in the understanding of aspirin's potential mechanisms in modulating reproductive processes and the role of inflammation in these processes. This review describes the collective findings of the EAGeR trial in the context of the existing literature regarding aspirin and inflammation in reproduction to inform relevant next steps in fertility and obstetric research, as well as potential implications for clinical care.
Keywords: aspirin; inflammation; implantation